Exploring Environmental Costs in Environmental Pollution Prevention Efforts: A Case Study of the Shalempang Batik MSME - Budianto, Ahmad Alfian; Herawati, Nurul; Seputro, Hanif Yusuf (Jati: Jurnal Akuntansi Terapan Indonesia, 2025)
This study aims to explore the environmental costs incurred by Batik Shalempang micro, small, and medium enterprises (MSMEs). This study used a qualitative case study. Three informants were recruited. Environmental cost exploration is identified and classified based on the categories of Hansen & Mowen (2009), including environmental prevention, environmental detection, environmental internal failure, and environmental external failure costs. Data collection procedures included interviews, observation, and documentation. The results of the identification and classification of environmental costs revealed that Batik Shalempang MSMEs have categories of prevention and internal failure costs. The incompleteness of these environmental cost categories is due to Batik Shalempang MSMEs focusing on initial management and waste reduction. In addition, MSMEs that are still micro entities also influence environmental cost expenditures. This study has limitations regarding financial data and records of MSMEs, as well as the knowledge of key informants regarding accounting and environmental costs. The implications of this study highlight the importance of education and outreach in addressing environmental issues and their impact on MSMEs. Additionally, it underscores the significance of basic accounting and record-keeping practices for MSMEs.